Band residual difference algorithm for retrieval of SO2 from the aura ozone monitoring instrument (OMI) - Krotkov, N.A; Carn, S.A; Krueger, A.J; Bhartia, P.K; Kai Yang, Kai Yang (IEEE transactions on geoscience and remote sensing, 2006)
[...] the diffuse boundaries of volcanic clouds can be imaged better and the clouds can be tracked longer.